Enterobiasis of the Ovary in a Patient With Cervical Carcinoma In Situ - Kevin McCabe; Patricia A. K. Nahn; Aysegul A. Sahin; Michele Follen Mitchell (Hindawi Limited, 1995)
Background: Enterobiasis occurs throughout the female genital tract and may involve peritoneal surfaces. It is generally an incidental finding at surgery or at autopsy but occasionally is symptomatic. Most of the superficial lesions are composed of granulomas with variable fibrosis in which diagnostic eggs are found, often associated with degenerated adult worms. Multiple histologic sections may be required to establish the diagnosis in older lesions.